Gathering and Apply Guidelines for TeleSpider Design for Urban Search and Rescue Applications on a Mobile Robot - Stepanova, Ekaterina R.; Heyde, Markus von der; Kitson, Alexandra; Schiphorst, Thecla; Riecke, Bernhard E. (Human-Computer Interaction. Interaction Contexts (HCI 2017), 2017)
Robotics technology can assist Urban Search and Rescue (USAR) by allowing to explore environments inaccessible or unsafe for a human team [1]. This creates the need to develop a better understanding of the USAR procedures and specific requirements in order to guide the design of the robotics technology which will be accepted by USAR professionals. The current paper explores the specific requirements for the assistive technology, and extracts design guidelines for development of the robotic technology to be used during USAR operations. Design guidelines are derived from both literature review and from a qualitative study performed with Vancouver Heavy Urban Search and Rescue Task Force (HUSAR), focusing on usage scenarios and specific requirements for communication, control and user experience. The study revealed that the most crucial factors for the design of the robot are speed, robustness, reliability, weight, affordability, and adaptability to different environments and tasks, as well as ability to provide a two-way audio/video communication. For the interface, the most important characteristics are its learnability, immersiveness, and ability to afford a high sense of spatial presence. We further discuss how the above requirements were implemented though a case-study of the development of the “TeleSpider” (a hexapod tele-operated walking robot), and assess its effectiveness during the field testing at the Vancouver HUSAR warehouse. Failing to meet a number of the discussed requirements will likely result in the technology to be rejected by the USAR team, and never being used during actual deployments as has happened with a number of existing technologies.
Keywords: Archiact; NSERC DG 2026; NSERC ENGAGE; Riecke; Riecke_2017; alex-kitson; bernhard-riecke; book-chapter; katerina-stepanova; markus-von-der-heyde; telespider; thecla-schiphorst